2011
DOI: 10.1177/0164027511411308
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Spiritual Needs in Health Care Settings

Abstract: Recognizing that spiritual needs often emerge in health care settings, the Joint Commission requires spiritual assessments in numerous organizations frequented by older adults. Given that many gerontological practitioners have received little training in identifying spiritual needs, a qualitative meta-synthesis (N = 9 studies) was conducted to identify and describe older adults' perceptions of their spiritual needs in health care settings. Five interrelated categories emerged: (a) spiritual practices; (b) rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 80 publications
2
35
0
Order By: Relevance
“…Three metasyntheses were returned uniquely by Embase (Agudelo‐Suarez et al, ; Cook et al, ; Heaton et al, ). Eight metasyntheses (Birnbaum and Saini, ; Cohen and Collens, ; Corcoran et al, ; Dillon et al, ; Gill and Fox, ; Hodge et al, ; Malpass et al, ; York and Wiseman, ) were returned uniquely by PsycINFO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three metasyntheses were returned uniquely by Embase (Agudelo‐Suarez et al, ; Cook et al, ; Heaton et al, ). Eight metasyntheses (Birnbaum and Saini, ; Cohen and Collens, ; Corcoran et al, ; Dillon et al, ; Gill and Fox, ; Hodge et al, ; Malpass et al, ; York and Wiseman, ) were returned uniquely by PsycINFO.…”
Section: Resultsmentioning
confidence: 99%
“…For example, two metasyntheses (Hodge et al, ; Lawrence et al, ) used a constant comparative approach (Glaser and Strauss, ), traditionally identified with grounded theory, to analyse themes. This resulted in identification of meaningful clusters of themes and relationships within those clusters of themes and, finally, the identification of the emergent third‐order constructs that formed the basis of the final metasynthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies with samples primarily comprised of both African Americans (Conner & Eller, 2004;Taylor et al, 2007) and European Americans (Hodge et al, 2012) have highlighted the importance of front line medical personnel in meeting clients' spiritual needs. Nurses (Nixon & Narayanasamy, 2010) and physicians (Ellis & Campbell, 2004) play a particularly prominent role in service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Some common needs among African Americans include treatment decisions related to euthanasia, life-sustaining treatments, and advance directives (Johnson et al, 2005). In keeping with their specialized knowledge in these and similar areas, physicians, nurses, staff members administering tests, and discharge planners can play an important role responding to clients' spiritual needs in this area through their attitudes and interactions (Cavendish et al, 2006;Hodge, Horvath, Larkin, & Curl, 2012).…”
Section: Failure To Address African Americansmentioning
confidence: 99%